Analysis of the teaching methods, approaches and techniques employed in Magic Book 2 - Papadaki, Aggeliki; Karagianni, Eleni (Eximia, 2023)
The purpose of this article is to reflect on three lessons taught to Young Learners and identify the teaching approaches, methods and techniques used. In the first part, there is a description of the teaching situation. In the second part, there is an analysis of the teaching methods, approaches and techniques used, while the extent to which they agree with how learners learn L2 is presented, too. In the third part, there is an activity suggested to supplement the lessons.